Herzen contra Marx: In search for a diagonal - A. V. Shabaga (RUDN journal of Sociology, 2023)
The first half of the 19th century was a period of dissidence and alternative social movements in Europe. The most famous and influential dissidents were A.I. Herzen and K. Marx. Both were supporters of socialism and founded movements that were destined to radically change the social life of the European East and West. They developed those social constructs of the future that are still in demand, since socialist and social-democratic ideas largely determine the contemporary political landscape. At first, both supported liberalism but later declared it unconstructive. Herzen criticized liberals for inventing the people rather than studying them and for demanding that everyone would become homo politicus to solve social problems. Marx became a preacher of dictatorship as the only way to build a just society in Europe, and often practiced authoritarianism which Herzen criticized. Herzen also criticized liberalism for its latent individualism and searched for a path to democratically reorganize the Russian society, which he considered mainly in the collectivist spirit. The author focuses on Herzen’s attempt to prove the possibility of bypassing the bourgeois formation of Marx by a ‘diagonal’ transition from pre-capitalism to socialism. Herzen considered capitalism a social failure, a ‘historical dislocation’ that developed in Western Europe but affected all peoples of the world. Herzen proposed an alternative construct with a certain potential for anticapitalist associations constantly emerging in various regions of the world - they try to create selfgoverning communities free from the shortcomings of bourgeois democracy.